2017
DOI: 10.1002/pen.24749
|View full text |Cite
|
Sign up to set email alerts
|

UV‐laser marking of a TiO2‐containing ABS material

Abstract: Marking of titanium dioxide‐containing ABS polymeric samples was accomplished using a UV laser that induces a white to grey color change with only a minor alteration of the plastic material. The characterization of this marking process has been conducted by different techniques to determine the quality of the UV‐laser marking and to gain an insight into how the plastic material is affected by laser irradiation. Surface characterization was performed and tests were conducted to evaluate the potential applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Clemente et al used a frequencytripled Nd:YAG laser emitting at 355 nm to produce aesthetical marks on white ABS. They found that the marks had a good level of scratch resistance similar to that of pad-painted marks and a good level of resistance to chemical agents and climate tests [48].…”
Section: Laser Marking Systemsmentioning
confidence: 95%
“…Clemente et al used a frequencytripled Nd:YAG laser emitting at 355 nm to produce aesthetical marks on white ABS. They found that the marks had a good level of scratch resistance similar to that of pad-painted marks and a good level of resistance to chemical agents and climate tests [48].…”
Section: Laser Marking Systemsmentioning
confidence: 95%
“…Laser marking is characterized by noncontact processing. The laser with a wavelength of 1064 nm is a more commonly used laser in the industry and is suitable for materials such as metal, ceramics, wood, and plastic. Compared with the easy carbonization and high char residue features of polycarbonate and polystyrene, it is rather difficult to perform laser marking with PP itself due to the poor absorption of the near-infrared laser energy of the 1064 nm wavelength. Usually, the method of adding laser marking additives can effectively improve the laser marking performance of PP.…”
Section: Introductionmentioning
confidence: 99%
“…A strongly developed tendency of applications for this type of electromagnetic radiation is laser marking. This method allows graphic signs to be obtained in the form of letters, numbers, symbols, barcodes, or drawings on the surfaces of various materials, including metals [25], wood [26], ceramics [27], and plastics [28]. Laser marking makes it possible to obtain graphic signs that are resistant to abrasion, water, and air humidity [29,30]; in addition, it has a positive effect on the environment, reducing the amount of material used in conventional decoration methods such as printing, padding, painting, and in-mold labeling (IML) [31].…”
Section: Introductionmentioning
confidence: 99%